2015
DOI: 10.1002/jor.23069
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine attenuates ACL transection and medial menisectomy‐induced cartilage destruction by inhibition of cystine/glutamate antiporter

Abstract: We had previously demonstrated that excitatory amino acid glutamate plays a role in the progression and severity of knee osteoarthritis (OA), and early hyaluronic acid injection attenuates the OA progression by attenuation of knee joint glutamate level, which was also related to the cystine/glutamate antiporter system X (system X À C ) expression. System X À C uptakes cystine into chondrocytes for glutathione (GSH) synthesis, but the role of system X À C in OA is rarely addressed. Sulfasalazine (SSZ) is a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Following the previous reports, OA was induced in rats [ 47 , 48 , 49 ]. The ACLT + MMx method was employed to induce OA in rats, and surgery on the right knee joint was performed ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Following the previous reports, OA was induced in rats [ 47 , 48 , 49 ]. The ACLT + MMx method was employed to induce OA in rats, and surgery on the right knee joint was performed ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tsai et al have investigated the action of Sxc- in the onset of knee osteoarthritis (OA) in rats after anterior cruciate ligament transection and medial meniscectomy (ACLT + MMx). They have observed that the intra-articular application of SSZ reduced knee swelling and cartilage destruction in the knees of ACLT + MMx rats and this action was blocked by NAC [130]. Nishio et al have observed the actions of ROS on synaptic transmission in rat spinal cord substantia gelatinosa (SG) neurons using whole-cell patch-clamp recordings.…”
Section: Nac In Neuropathic Painmentioning
confidence: 99%
“…Such an analysis may provide new strategies for the future management of knee conditions, particularly early management of knee injuries. As demonstrated in our previous serial studies using an ACL transaction and partial medial meniscectomy rat model, early medical intervention delays OA development [4648]. These findings may provide a new strategy for the early management of knee injuries that may reduce the disease burden, lower the incidence of knee arthroplasty and reduce NHI expenses.…”
Section: Discussionmentioning
confidence: 56%